2012
DOI: 10.1177/0165025412448605
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional examination of the acculturation and psychological functioning of a sample of immigrant Chinese mothers in the US

Abstract: The present research used the cluster analysis method to examine the acculturation of immigrant Chinese mothers (ICMs), and the demographic characteristics and psychological functioning associated with each acculturation style. The sample was comprised of 83 first-generation ICMs of preschool children residing in Maryland, Unites States (US). Cluster analysis revealed four acculturation styles: psychologically-behaviorally integrated; psychologically-behaviorally assimilated; psychologically-behaviorally undif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
1
13
1
Order By: Relevance
“…This consistency was surprising given the distinction between behavioral and psychological acculturation processes (Ward & Kus, 2012), but may have been due to the lack of statistical power and representation of the local CIM group with its small sample size (83 CIMs). We expected to find similar acculturation components (e.g., undifferentiated) in CIMs as those previously uncovered by Tahseen and Cheah (2012) because the study sampled CIMs from a similar geographic area as the current study, but also anticipated more differences between CIMs' behavioral and psychological acculturation to emerge with a larger sample in the current study. Choi et al (2016) identified three acculturation profiles and found that the integrated style was most prevalent in a sample comprised mostly of second-generation Korean American adolescents in Chicago.…”
Section: Acculturation Componentsmentioning
confidence: 53%
“…This consistency was surprising given the distinction between behavioral and psychological acculturation processes (Ward & Kus, 2012), but may have been due to the lack of statistical power and representation of the local CIM group with its small sample size (83 CIMs). We expected to find similar acculturation components (e.g., undifferentiated) in CIMs as those previously uncovered by Tahseen and Cheah (2012) because the study sampled CIMs from a similar geographic area as the current study, but also anticipated more differences between CIMs' behavioral and psychological acculturation to emerge with a larger sample in the current study. Choi et al (2016) identified three acculturation profiles and found that the integrated style was most prevalent in a sample comprised mostly of second-generation Korean American adolescents in Chicago.…”
Section: Acculturation Componentsmentioning
confidence: 53%
“…They may also experience less acculturative stress (Oh et al, 2002) and be able to draw resources from both Chinese and American cultures and have larger social support networks that can buffer them from psychological maladjustment (e.g., negative moods, loneliness). In contrast, separated mothers may only be able to obtain support from the relatively smaller and more dispersed Chinese community in Maryland (Tahseen & Cheah, 2012), and suffer from rejection or acculturative stress that exacerbates their depressive symptoms (Hwang & Ting, 2008). However, due to the cross-sectional design, we cannot rule out the possibility that mothers’ poorer psychological well-being may preclude their engagement in the larger mainstream culture, which may require additional psychological resources.…”
Section: Discussionmentioning
confidence: 99%
“…Future examination of psychological acculturation, which reflects individuals’ identification with values, norms, beliefs, and attitudes of the two cultures (Berry, 1992; Birman & Tran, 2008) and its relations to parents’ psychological adjustment and parenting behaviors are warranted. It will be also crucial to consider both behavioral and psychological acculturation when creating acculturation profiles such that both classic and newly identified acculturation strategies may be better represented and their associations with immigrants’ psychological adjustment and parenting can be better delineated (Chia & Costigan, 2006; Tahseen & Cheah, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the predominant research emphasis on Asian Americans and immigrants has been on their academic achievement, resulting in little empirical attention given to the health conditions in this group (Juang, Qin, & Park, 2013; Tahseen & Cheah, 2012). Even though Asian Americans have been reported to have lower rates of overweight and obesity compared to non-Asian Americans, there is a general failure to recognize the diverse levels of health status among this heterogeneous group (Jain et al, 2012), likely because of the model minority stereotype depicting Asian Americans as having adapted successfully to the larger American culture (Matloff, Lee, Tang, & Brugge, 2008).…”
Section: Macrosystem: Cultural Ethnotheories and Societal Attitudesmentioning
confidence: 99%